2019
DOI: 10.1038/s41590-019-0502-2
|View full text |Cite
|
Sign up to set email alerts
|

Slow phosphorylation of a tyrosine residue in LAT optimizes T cell ligand discrimination

Abstract: Self/non-self discrimination is central to T cell-mediated immunity. The kinetic proofreading model can explain T cell antigen receptor (TCR) ligand discrimination; however, the rate-limiting steps have not been identified. Here, we show that tyrosine phosphorylation of the T cell adaptor protein LAT at position Y132 is a critical kinetic bottleneck for ligand discrimination. LAT phosphorylation at Y132, mediated by the kinase ZAP-70, leads to the recruitment and activation Users may view, print, copy, and dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(137 citation statements)
references
References 61 publications
8
117
1
Order By: Relevance
“…Again, mutation of glycine 131 to aspartate induced increased kinetics and intensity of Erk phosphorylation, with statistical significance at the 3 min time point ( Figure 1C, lower diagram). Altogether, these data confirm that the LAT G131D mutation releases the brake imposed on the TCR/CD3 signaling cassette, as previously observed by Lo et al (2019).…”
Section: Mutation Of Gly 131 To Asp Of Lat Increases Intracellular Sisupporting
confidence: 89%
See 2 more Smart Citations
“…Again, mutation of glycine 131 to aspartate induced increased kinetics and intensity of Erk phosphorylation, with statistical significance at the 3 min time point ( Figure 1C, lower diagram). Altogether, these data confirm that the LAT G131D mutation releases the brake imposed on the TCR/CD3 signaling cassette, as previously observed by Lo et al (2019).…”
Section: Mutation Of Gly 131 To Asp Of Lat Increases Intracellular Sisupporting
confidence: 89%
“…To study the role of the conserved glycine residue preceding tyrosine 132 in LAT we generated lentiviral plasmids to express wild-type LAT or a LAT G131D mutant in J.CaM2 cells, as previously described (Arbulo-Echevarria et al, 2016. This would allow us to verify the effects observed by Lo et al (2019). in Jurkat cells in which CRISPR was performed to eliminate the Lat gene in both chromosomes, and also address other questions of interest.…”
Section: Generation Of Lentiviral Transfectants Of J Cam2 Cells Exprmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to acting between two proteins, regulated unbinding is likely to operate on stable phase-separated signalling assemblies formed by weakly binding multi-domain proteins (55,56). Interestingly, activated ZAP70 catalyses the formation of LAT signalling assemblies (57) and recently, it has been suggested that LAT may be a proofreading step (58,59). Consistent with this, in vitro generated LAT assemblies displayed long half-lives without phosphatases but were disassembled within minutes in their presence (57).…”
Section: Discussionmentioning
confidence: 85%
“…ZAP-70-targeted sites are characterized by multiple negative residues surrounding the phosphorylated tyrosine; indeed, ZAP-70 is deterred from phosphorylating substrate motifs containing a positive charge anywhere within the surrounding motif [65]. The presence of glycine at the Y-1 position also slows substrate phosphorylation by ZAP-70 [55]. Gads Y45 is preceded by glycine at the Y-1 position, followed by a lysine at the Y+3 position, and has only one negatively charged residue in the surrounding motif, strongly suggesting that it is not a substrate of ZAP-70.…”
Section: P9mentioning
confidence: 99%